2020
DOI: 10.1097/mnh.0000000000000567
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal for the management of pruritus and uremic toxins in patients with chronic kidney disease

Abstract: Purpose of the review: Pruritus is an important, prevalent but often neglected symptom in patients with advanced CKD or on dialysis,. This review addresses the use of activated charcoal and its analogs in the treatment of uremic pruritus, which can be a marker of uremic toxicity. Recent findings: When common causes are corrected and dialysis efficiency is optimized, pruritus is mainly ascribed to the retention of middle and protein-bound molecules, of which indoxyl sulfate and p-Cresyl sulfate are the best stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 77 publications
0
26
0
Order By: Relevance
“…summarize existing data and conclude that, although the evidence is limited, both oral activated charcoal and HD or hemoperfusion with an activated charcoal cartridge may have a role in the treatment of CKDaP. 81 …”
Section: Diagnosismentioning
confidence: 98%
See 1 more Smart Citation
“…summarize existing data and conclude that, although the evidence is limited, both oral activated charcoal and HD or hemoperfusion with an activated charcoal cartridge may have a role in the treatment of CKDaP. 81 …”
Section: Diagnosismentioning
confidence: 98%
“…80 In a recent review, Cupisti et al summarize existing data and conclude that, although the evidence is limited, both oral activated charcoal and HD or hemoperfusion with an activated charcoal cartridge may have a role in the treatment of CKDaP. 81 Hyperparathyroidism and high calcium, magnesium, and phosphorus levels have been associated with CKD-aP, and a few small studies suggest that decreasing the levels of these potential pruritogens may decrease itching. 61,82 A prospective, uncontrolled study of 37 dialysis patients with secondary hyperparathyroidism (mean PTH level, 1473 pg/ml), of which 22 had pruritus, found that parathyroidectomy significantly decreased itching.…”
Section: Xerosismentioning
confidence: 99%
“…Systemic inflammation caused by pruritogens (accumulated uremic toxins, histamines, and proinflammatory cytokines) and the imbalance of the opioid system are considered to be possible pathogenesis of UP [5,50]. The accumulated uremic toxins can destroy the intestinal barrier integrity, cause dysbiosis of the gut, and progressive kidney damage [50,51]. Toxins, including mineral products and uremic toxins, were proposed as pruritogens [4].…”
Section: Discussionmentioning
confidence: 99%
“…Kt/V has been found to be inversely related to CKD-aP [ 40 ]. Higher dialysis improves the prevalence and intensity of pruritus in hemodialyzed patients [ 65 ]. Neutral macroporous resin hemoperfusion (HP) was used in a study to treat maintenance hemodialysis patients (MHD) with refractory uremic pruritus.…”
Section: Treatmentmentioning
confidence: 99%
“…Oral charcoal is most frequently associated with side effects such as appetite loss, nausea, constipation, and gastrointestinal discomfort [ 67 ]. In a study, cholestyramine, a nonabsorbable anion-exchange resin, which binds organic acids intraluminally, has been found effective in relieving CKD-aP [ 65 ].…”
Section: Treatmentmentioning
confidence: 99%